Mitigation of Sodium Iodate-Induced Cytotoxicity in Retinal Pigment Epithelial Cells in vitro by Transgenic Erythropoietin-Expressing Mesenchymal Stem Cells - Koh, Avin Ee-Hwan; Subbiah, Suresh Kumar; Farhana, Aisha; Alam, Mohammad Khursheed; Mok, Pooi Ling (Frontiers in Cell and Developmental Biology, 2021)
Mesenchymal stem cells (MSC) have shown promise in restoring the vision of patients in clinical trials. However, this therapeutic effect is not observed in every treated patient and is possibly due to the inefficacies of cell delivery and high cell death following transplantation. Utilizing erythropoietin can significantly enhance the regenerative properties of MSCs and hence improve retinal neuron survivability in oxidative stress. Hence, this study aimed to investigate the efficacy of conditioned medium (CM) obtained from transgenic human erythropoietin-expressing MSCs (MSCEPO) in protecting human retinal pigment epithelial cells from sodium iodate (NaIO3)-induced cell death. Human MSC and MSCEPO were first cultured to obtain conditioned media (CM). The IC50 of NaIO3 in the ARPE-19 culture was then determined by an MTT assay. After that, the efficacy of both MSC-CM and MSC-CMEPO in ARPE-19 cell survival were compared at 24 h and 48 h after NaIO3 treatment with MTT. The treatment effects on mitochondrial membrane potential was then measured by a JC-1 flow cytometric assay. The MTT results indicated a corresponding increase in cell survivability (5% – 58%) in the ARPE-19 cell cultures. In comparison to MSC-CM, the use of conditioned medium collected from the MSC-CMEPO further enhanced the rate of ARPE-19 survivability at 24 h (P<.05) and 48 h (P<.05) in the presence of NaIO3. Furthermore, more than 90% were found viable with the JC-1 assay after MSC-CMEPO treatment, showing a positive implication on the mitochondrial dynamics of ARPE-19. The MSC-CMEPO provided an enhanced mitigating effect against NaIO3-induced ARPE-19 cell death over that of MSC-CM alone during the early phase of the treatment, and it may act as a future therapy in treating retinal degenerative diseases.